Psychosomatic regularities of psychotic disorders of women in involution (pathogenesis, clinics, psychodynamic psychotherapy) - М. М. Pustovoyt (Zaporožskij Medicinskij Žurnal)
The problem of psychotic disorders with onset in the age of involution from broader perspective, guided by modern multidimensional paradigm, was never discussed before. Involutional psychosis is considered as a constellation of the biological changes that are irrefutable in this age period. Certain personality traits and coping strategies can be predisposing to psychotic response, as well as typical features of the “life curve” and external stressors that can run a psychotic reaction. The paper presents the result of our study. This study pays much attention to study of premorbid personality, with emphasis on characteristic features, peculiarities of the emotional reaction and motivation-behavioral area, which completely coincided with characteristics of the narcissistic personality disorder listed in DSM-V (2013).